Circulating N-Acetylaspartate Levels Associate with Measures of Peripheral and Tissue-Specific Insulin Sensitivity - Rebelos, Eleni; Honka, Miikka-Juhani; Latva-Rasku, Aino; Rajander, Johan; Salminen, Paulina; Anastasiou, Ioanna A.; Kounatidis, Dimitris; Tentolouris, Nikolaos; Campi, Beatrice; Dardano, Angela; Daniele, Giuseppe; Saba, Alessandro; et al. (MDPI, 2025)
N-acetylaspartate (NAA) is the second most abundant metabolite in the human brain. Quantifiable amounts of NAA are also present in the blood, but its role in the peripheral tissues is largely unknown. First, we determined the acute effects of insulin administration on NAA concentrations; second, we assessed whether circulating NAA levels associate with markers of central and peripheral insulin sensitivity. A total of 24 persons living with obesity and 19 healthy, lean controls, without neurological disorders, underwent a euglycemic hyperinsulinemic clamp combined with fluorodeoxyglucose positron emission tomography ([18F]FDG-PET) imaging of the brain, abdomen, and femoral area. Plasma concentrations of NAA were measured at baseline and similar to 2 h into the clamp using high-performance liquid chromatography coupled with tandem mass spectrometry (HPLC-MS-MS). Glucose uptake (GU) rates were analysed using a fractional uptake rate. Serum acetate levels were also assessed using nuclear magnetic resonance (NMR) metabolomics. From baseline to steady-state, insulin levels increased from a mean level of 66 to 447 pmol/L (p < 0.0001). Over this period, circulating NAA concentrations decreased by 5% (p = 0.01), similarly in both groups. The change in NAA was inversely related with the change in plasma acetate (r = -0.36, p = 0.048). Circulating NAA was associated with waist-hip ratio (rho = -0.54, p = 0.0002), steady-state free fatty acids (rho = -0.44, p = 0.003), and directly with HDL cholesterol (rho = 0.54, p = 0.0002), adiponectin (rho = 0.48, p = 0.003), and whole-body insulin sensitivity (rho = 0.34, p = 0.03). Circulating NAA was directly related with skeletal muscle (rho = 0.42, p = 0.01) and visceral adipose tissue GU (rho = 0.41, p = 0.02). Insulin administration leads to a small decrease in circulating NAA levels, and NAA associates consistently with markers of insulin sensitivity. While plasma NAA may be relevant to aspects of whole-body homeostasis, mechanistic insights are needed.